Interplay between collagen hydrolysates and the ability of FKBP35 from Plasmodium knowlesi in preventing insulin aggregation - Nur Iliyana Illang; Goh, Carlmon Kah Wun; Muhammad Arifin; Cahyo Budiman (Penerbit Universiti Kebangsaan Malaysia, 2025)
FK506-binding protein 35 (FKBP35) from Plasmodium knowlesi (Pk-FKBP35) is a potential target for combating the surge in simian malaria cases. While previously speculated to hinder protein synthesis aggregation within parasite cells, this study seeks to experimentally validate the capacity of Pk-FKBP35 to avert protein aggregation. Additionally, it aims to examine the influence of collagen hydrolysates (CH) on this ability. Initially, Pk-FKBP35 was overexpressed in Escherichia coli BL21(DE3) and subsequently purified. To assess its capacity for preventing aggregation, a dithiothreitol (DTT)-induced insulin aggregation assay was conducted and observed via SDS-PAGE. The findings showed a concentration-dependent inhibition by Pk-FKBP35 against DTT-induced insulin aggregation. At the concentration of 0.75 mg/mL of Pk-FKBP35, the amount of soluble insulin was increased to about 5-fold higher. Interestingly, in the presence of FK506, Pk-FKBP35’s ability to prevent insulin aggregation remains intact. Since FK506 is known to specifically bind to the catalytic domain of Pk-FKBP35, this suggests that the region responsible for the protein’s aggregation prevention activity is independent from the catalytic domain. Moreover, when coupled with CH derived from bovine, bone broth, fish, and swine, Pk-FKBP35’s effectiveness in preventing DTT-induced insulin aggregation was attenuated, albeit to varying degrees. Notably, swine and bone broth CH exhibited superior inhibition of aggregation prevention compared to bovine and fish CH. This study validates Pk-FKBP35’s capability to impede protein aggregation, showcasing a promising potential for inhibition by CH, particularly those sourced from swine and bone broth.